Dispersal and organization of polarized cells: non-linear diffusion and cluster formation without adhesion. (21st September 2021) - Nakamura, G; Badoual, M; Fabiani, E; Deroulers, C
Abstract: Experimental studies of cell motility in culture have shown that under adequate conditions, these living organisms possess the ability to organize themselves into complex structures. Such structures may exhibit a synergy that greatly increases their survival rate and facilitates growth or spreading to different tissues. These properties are even more significant for cancer cells and related pathologies. Theoretical studies supported by experimental evidence have also shown that adhesion plays a significant role in cellular organization. Here, we show that the directional persistence observed in polarized displacements permits the formation of stable cell aggregates in the absence of adhesion, even in low-density regimes. We introduce a discrete stochastic model for the dispersal of polarized cells with exclusion and derive the hydrodynamic limit. We demonstrate that the persistence coupled with the cell–cell exclusion hinders the cellular motility around other cells, leading to a non-linear diffusion which facilitates their capture into larger aggregates.